Georgia : Sixth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Georgia. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Sixth Review Under the Poverty Reduction and Growth Facility (PRGF) for Georgia. Economic performance in recent years has been impressive, with the establishment of macroeconomic stability, a dramatic fiscal turnaround, and remarkable improvements in governance and the business environment. The original targets under the PRGF arrangement have been reached or exceeded. All quantitative performance criteria for the final review were met. Given the authorities' strong performance, IMF staff supports the completion of the Sixth Review and the request for a waiver.